A comparison of anti-HER2 IgA and IgG1 in vivo efficacy is facilitated by high N-glycan sialylation of the IgA. Issue 1 (2nd January 2016) - Rouwendal, Gerard JA; van der Lee, Miranda M; Meyer, Saskia; Reiding, Karli R; Schouten, Jan; de Roo, Guy; Egging, David F; Leusen, Jeanette HW; Boross, Peter; Wuhrer, Manfred; Verheijden, Gijs F; Dokter, Wim H; et al.
Abstract : Monomeric IgA has been proposed as an alternative antibody format for cancer therapy. Here, we present our studies on the production, purification and functional evaluation of anti-HER2 IgA antibodies as anti-cancer agents in comparison to the anti-HER2 IgG1 trastuzumab. MALDI-TOF MS analysis showed profound differences in glycosylation traits across the IgA isotypes and cell lines used for production, including sialylation and linkage thereof, fucosylation (both core and antennary) and the abundance of high-mannose type species. Increases in sialylation proved to positively correlate with in vivo plasma half-lives. The polymerization propensity of anti-HER2 IgA2m2 could be suppressed by an 18-aa deletion of the heavy chain tailpiece - coinciding with the loss of high-mannose type N-glycan species - as well as by 2 cysteine to serine mutations at positions 320 and 480. The HER2 F(ab')2-mediated anti-proliferative effect of the IgA2m1 and IgA2m2 subtypes was similar to IgG1, whereas the IgA1 isotype displayed considerably lower potency and efficacy. The Fc-mediated induction of antibody-dependent cell-mediated cytotoxicity (ADCC) using human whole blood ADCC assays did not demonstrate such clear differences between the IgA isotypes. However, the potency of the anti-HER2 IgA antibodies in these ADCC assays was found to be significantly lower than that of trastuzumab. In vivo anti-tumor activity of the anti-HER2 IgA antibodies was compared to that of trastuzumab in a BT-474 breast cancer xenograft model. Multiple dosing and sialylation of the IgA antibodies compensated for the short in vivo half-life of native IgA antibodies in mice compared to a single dose of IgG1. In the case of the IgA2m2 antibody, the resulting high plasma exposure levels were sufficient to cause clear tumor stasis comparable to that observed for trastuzumab at much lower plasma exposure levels.